PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DEPARTEMEN ASSEMBLY DI PT SUMMIT ADYAWINSA INDONESIA - Arsyka, Tania; Suherman, Enjang; Sungkono, Sungkono (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The amount of time taken to complete tasks and the lack of passion for them suggest that work discipline and motivation are not at their best, which has an influence on ignored work. The goal of this research is to examine the link between employee performance and work motivation and discipline. With a population of 209, a random sampling methodology was used to acquire 137 samples from which to draw conclusions. Observations and questionnaires were employed for data gathering, while SPSS software was used for data analysis. Workplace discipline and motivation were shown to have a partial and significant impact on performance, according to the findings. Motivating and disciplining employees is a good way to improve their performance.